(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2026)
The rapid digitalization of the criminal justice system in India has fundamentally transformed the manner in which criminal proceedings are initiated, investigated, prosecuted, and adjudicated. Technological innovations such as e-FIRs, electronic filing systems, virtual hearings, digital evidence management, video conferencing, artificial intelligence-assisted legal research, electronic summons, and online judicial databases have introduced unprecedented efficiency and transparency into criminal administration. The enactment of the Bharatiya Nagarik Suraksha Sanhita, 2023 (BNSS), Bharatiya Nyaya Sanhita, 2023 (BNS), and Bharatiya Sakshya Adhiniyam, 2023 (BSA) has accelerated this transformation by embedding digital procedures directly into substantive and procedural criminal law. These reforms have significantly altered the institutional role and functional responsibilities of public prosecutors in India. Traditionally, public prosecutors functioned primarily as courtroom advocates responsible for presenting evidence, examining witnesses, and assisting courts during trials. However, in the era of digital justice, prosecutors are increasingly expected to manage electronic evidence, supervise technologically sophisticated investigations, coordinate with cyber forensic experts, ensure compliance with digital procedural safeguards, conduct virtual prosecutions, and protect constitutional rights within technologically mediated judicial environments. The integration of digital tools has expanded prosecutorial accountability while simultaneously creating new ethical, procedural, and institutional challenges. This article critically examines the digitalization of criminal proceedings in India and analyzes its impact on the evolving role of public prosecutors. It explores the legal framework governing digital criminal justice, including the Information Technology Act, 2000, the e-Courts Mission Mode Project, the BNSS, and the Bharatiya Sakshya Adhiniyam. The study further evaluates how prosecutors are adapting to electronic evidence management, cybercrime litigation, virtual court proceedings, online witness examination, and data-driven prosecution systems. Special emphasis is placed upon prosecutorial responsibilities relating to privacy protection, cybersecurity, digital ethics, evidentiary integrity, and procedural fairness. The article also examines major judicial developments supporting virtual proceedings and electronic service of summons under the BNSS. Contemporary developments indicate that Indian courts increasingly recognize digital mechanisms such as video conferencing and electronic communication as legitimate components of criminal adjudication. The study concludes that digitalization has transformed the office of the public prosecutor from a traditional litigation-oriented institution into a technologically integrated component of modern criminal governance. While digital justice offers substantial benefits in terms of efficiency, accessibility, transparency, and case management, significant challenges remain regarding infrastructure, training, cybersecurity, digital inequality, and protection of fair trial rights. The article recommends comprehensive prosecutorial training, technological modernization, institutional safeguards, ethical regulation of artificial intelligence, and coordinated reforms to ensure that digital criminal justice remains constitutionally compatible and socially inclusive.